Cardiac outcomes after pregnancy in women with congenital heart disease. Issue 20 (11th October 2010) - Balint, Olga H; Siu, Samuel C; Mason, Jennifer; Grewal, Jasmine; Wald, Rachel; Oechslin, Erwin N; Kovacs, Brigitte; Sermer, Mathew; Colman, Jack M; Silversides, Candice K
Abstract : Objective: Women with congenital heart disease (CHD) are at risk for adverse cardiac events during pregnancy; however, the risk of events late after pregnancy (late cardiac events; LCE) has not been well studied. A study was undertaken to examine the frequency and determinants of LCE in a large cohort of women with CHD. Design: Baseline characteristics and pregnancy were prospectively recorded. LCE (>6 months after delivery) were determined by chart review. Survival analysis was used to determine the risk factors for LCE. Setting: A tertiary care referral hospital. Patients: The outcomes of 405 pregnancies were studied (318 women; median follow-up 2.6 years). Main outcome measures: LCE included cardiac death/arrest, pulmonary oedema, arrhythmia or stroke. Results: LCE occurred after 12% (50/405) of pregnancies. The 5-year rate of LCE was higher in women with adverse cardiac events during pregnancy than in those without (27±9% vs 15±3%, HR 2.2, p=0.02). Women at highest risk for LCE were those with functional limitations/cyanosis (HR 3.9, 95% CI 1.2 to 13.0), subaortic ventricular dysfunction (HR 3.0, 95% CI 1.4 to 6.6), subpulmonary ventricular dysfunction and/or significant pulmonary regurgitation (HR 3.2, 95% CI 1.6 to 6.6), left heart obstruction (HR 2.6, 95% CI 1.2 to 5.2) and cardiac events before or during pregnancy (HR 2.6, 95% CI 1.3 to 4.9). In women with 0, 1 or >1 risk predictors the 5-year rate of LCE was 7±2%, 23±5% and 44±10%, respectively (p<0.001). Conclusions: In women with CHD, pre-pregnancy maternal characteristics can help to identify women at increased risk for LCE. Adverse cardiac events during pregnancy are important and are associated with an increased risk of LCE.